+0

# f(x)=7^x then f(x+3)-f(x+1) equals

0
36
1

f(x)=7^x then f(x+3)-f(x+1) equals

Guest Nov 5, 2017

#1
+5261
+1

f(x)  =  7^x

f(x + 3)  =  7^(x + 3)     and     f(x + 1)  =  7^(x + 1)

So

f(x + 3) - f(x + 1)  =  7^(x + 3) - 7^(x + 1)

Remember that   xa * xb  =  xa+b  . So...

f(x + 3) - f(x + 1)  =  7^x  *  7^3  -  7^x  *  7^1

=  7^x  *  343  -  7^x  *  7             Factor out a  7^x  from both terms.

=  7^x  *  (343  -  7)

=  7^x  *  336

hectictar  Nov 5, 2017
Sort:

#1
+5261
+1

f(x)  =  7^x

f(x + 3)  =  7^(x + 3)     and     f(x + 1)  =  7^(x + 1)

So

f(x + 3) - f(x + 1)  =  7^(x + 3) - 7^(x + 1)

Remember that   xa * xb  =  xa+b  . So...

f(x + 3) - f(x + 1)  =  7^x  *  7^3  -  7^x  *  7^1

=  7^x  *  343  -  7^x  *  7             Factor out a  7^x  from both terms.

=  7^x  *  (343  -  7)

=  7^x  *  336

hectictar  Nov 5, 2017

### 6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details